2018
DOI: 10.1016/j.pedneo.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

The clinical characteristics and neurodevelopmental outcome of preterm infants with persistent periventricular echogenicity

Abstract: The clinical characteristics and neurodevelopmental outcomes of preterm infants with persistent PVE were not different from those of infants with normal findings. Our study supports the concept that persistent PVE without cystic change may be a benign finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Included infants were born at less than 34 weeks’ gestation or weighing less than 1500 g, between 1993 and 2015. 17 , 21 , 25 , 27 , 29 , 35 , 39 , 41 , 42 , 49 , 51 , 53 Of these studies, 8 provided data on neurodevelopmental impairment after cystic periventricular leukomalacia (cPVL) and 4 of these were suitable for meta-analysis. 27 , 39 , 49 , 51 They highlighted a significantly increased crude risk of moderate to severe neurodevelopmental impairment: OR 3.63, 95% CI (2.49–5.31) I 2 = 0% ( Table 2 ; Supplemental Fig 25 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Included infants were born at less than 34 weeks’ gestation or weighing less than 1500 g, between 1993 and 2015. 17 , 21 , 25 , 27 , 29 , 35 , 39 , 41 , 42 , 49 , 51 , 53 Of these studies, 8 provided data on neurodevelopmental impairment after cystic periventricular leukomalacia (cPVL) and 4 of these were suitable for meta-analysis. 27 , 39 , 49 , 51 They highlighted a significantly increased crude risk of moderate to severe neurodevelopmental impairment: OR 3.63, 95% CI (2.49–5.31) I 2 = 0% ( Table 2 ; Supplemental Fig 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…Only 1 study explored behavioral outcomes up to 3 years after WMI, and 3 explored speech and language outcomes. 21,33,38,49 Lean 2019 and Sarkar 2018 both reported a higher crude risk of language impairment after WMI. Lean 2019 reported a higher crude risk after IVH grade 3 to 4 or posthemorrhagic hydrocephalus or cPVL OR 2.53, which did not persist on adjusting for confounders.…”
Section: Behavioral and Speech And Language Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…When we attempt to use PVE to predict the neurologic outcome, it is best to homogenize the eligible population. Bae et al 5 demonstrated that there was a significantly higher incidence of late sepsis in the persistent PVE group. The role of late sepsis in persistent PVE and the final outcome should be clarified.…”
Section: What Is Pve?mentioning
confidence: 97%
“…This leads to widespread patterns of white and gray matter injury, altered neuro developmental trajectories, and associated neuro behavioral impairments in motor, cognitive, and social-emotional functioning, which are collectively referred to as encephalopathy of prematurity (Kinney & Volpe, 2012;Volpe, 2009b). Among babies who are born preterm who do not have periventricular leukomalacia, many have high echogenicity, or brightness in the periventricular region seen on serial head ultrasounds during the neonatal period (Bae et al, 2018). Persistence of this echogenicity on head ultrasounds (i.e., ≥ 14 days) is associated with the presence of any kind of infection (e.g., sepsis).…”
Section: Preterm Birthmentioning
confidence: 99%